EVALUASI PENGGUNAAN ANTIBIOTIK PNEUMONIA DENGAN METODE ATC/DDD PADA PASIEN PEDIATRI DI INSTALASI RAWAT INAP RSUD. DR. A. DADI TJOKRODIPO BANDAR LAMPUNG TAHUN 2019 - Lilik Koernia Wahidah; Novita Tri Wahyuni; Deska Maharani Putri (Fakultas MIPA Universitas Tulang Bawang Lampung, 2020)
ABSTRACT Pneumonia is an inflammation of the lungs that causes pain during breathing and limited oxygen intake. Antibiotics are the main therapy for pneumonia, appropriate and rational antibiotic therapy will determine the success of treatment to avoid bacterial resistance. The purpose of this study was to evaluate the use of pneumonia antibiotics in pediatric patients with the ATC / DDD method in pediatric patients in the Hospital Dr. Hospital. A. Dadi Tjokrodipo Bandar Lampung in 2019. This research is descriptive in nature with retrospective data collection. The sampling technique used was purposive sampling with a sample size of 70 patients with pediatric pneumonia. The data obtained were analyzed by using ATC / DDD and DU 90% methods. The results showed that from 70 samples studied, it was found that the patient characteristics were based on gender, namely 61.42% of them were male and based on age, namely 65.71% were infant patients aged 1 month - 2 years. The total use of antibiotics was 65.92 DDD / 100 days of hospitalization and antibiotics that entered the 90% DU segment, namely ampicillin (27.53 DDD / 100 days of hospitalization), gentamicin (8.39 DDD / 100 days of hospitalization), azithromycin (7 , 13 DDD / 100 days of care), amoxicillin (6.88 DDD / 100 days of hospitalization) and ampicillin sulbactam (6.6 DDD / 100 days of hospitalization). Then evaluated the use of antibiotics and the results were 100% correct, 100% correct indication, 57.4% correct dose and 100% correct time interval of administration. The use of antibiotic pneumonia in Dr. A. Dadi Tjokrodipo still needs to be improved again, especially regarding the administration of antibiotic doses. Keywords: Antibiotics, ATC, DDD, Pediatrics, Pneumonia.